L1 Interference and Pronunciation Difficulties among Pre-service EFL Teachers in Indonesia - Andriani, Agis; Saeful Anwar; Sitti Syakira (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
Pronunciation plays a critical role in English as a Foreign Language (EFL) learning, as it directly influences learners’ communication fluency and comprehensibility. However, in the Indonesian EFL context, many pre-service English teacher students continue to experience pronunciation difficulties, which are commonly influenced by their first language (L1), limited early exposure to English, and the complexity of English phonology. This study aimed to investigate the types of pronunciation difficulties faced by pre-service English teacher students, the influence of L1 interference on their English pronunciation, and the strategies they employ to overcome these challenges. This research combined qualitative thematic analysis and acoustic phonetic analysis, involved four pre-service English teacher students from diverse regional language backgrounds, Sundanese, Javanese, Buginese, and Ambonese Malay. Data were collected through semi-structured interviews conducted online via Zoom, and vowel formant analysis was conducted using PRAAT software to compare the participants’ vowel production with native speaker benchmarks. The data analyzed using thematic analysis framework revealed five central themes: (1) perceived pronunciation difficulties and language awareness, (2) challenges with English phonemes absent in L1, (3) the influence of L1 stress, rhythm, and intonation, (4) pronunciation learning strategies including classroom practices, and (5) motivation linked to professional identity. Additionally, motivation emerged as a significant factor in improving pronunciation. The PRAAT analysis confirmed that the participants’ L1 backgrounds strongly influenced variations in vowel production. It concludes that L1 interference significantly shapes pronunciation difficulties, while self-awareness, motivation, and active learning strategies play essential roles in mitigating these challenges.